THE DART BOARD MEDIA TO IMPROVE LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Deni Dayanti; Berlyan Salsabilla Anindyta Susanto; Desta Anggi Fauziah; Diah Anggun Pratiwi; Dewi Rohmaningsih; Denita Sekarningrum; Sri Suwartini; Iisrohli Irawati (El Midad, 2025)
This study aims to improve the learning outcomes of class IVB students of SD Negeri 2 Prambanan by using Dart Board media in learning Natural and Social Sciences (Ipas) on the material of Indonesian Cultural Wealth. This research is a Classroom Action Research (CAR), which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were class IVB students of SD Negeri 2 Prambanan in the 2024/2025 Academic Year. Data were collected through learning outcome tests, observations, and questionnaires. Data analysis was carried out using quantitative and qualitative approaches to measure improvements in learning outcomes and student responses to the use of Dart Board media. The results showed that using Dart Board media significantly improved student learning outcomes. In cycle I, the average student score increased from 68.69 in the pre-cycle stage to 79.47, while in cycle II it increased again to 82.63. In addition, students showed active involvement and positive responses to learning with this media. Thus, Dart Board media can be an innovative alternative in science learning to improve student learning outcomes and make the learning atmosphere more enjoyable and interactive.